(untitled) (Biological Sciences - PJSIR, 2022)
The life span of melted Philips torch has been extended for laboratory use by modifying the damaged Philips torch and then compared with that ofa standard Philips torch. The construction of the modified torch is simple, easy to assemble and replace, and is ideally suited for the analysis of sample solutions by inductively coupled plasma spectrometry. Evaluation of the modified torch reduced cost, usually caused by constant melting of ICP torch and also gave similar results in terms of precision, sensitivity and detection limits when compared with the conventional new ICPPhilips torch (type 145).